Seismic performance sensitivity analysis to random variables for cable tray system - Fu, Zhaoyang; Wu, Siyuan (Journal of Civil Engineering and Management, 2024)
Random variables introduced in modelling of seismic engineering are often the result of cognitive limitations and the unpredictability of structures, leading to uncertainties in the field. A practical method for dealing with them is to develop sensitivity analysis in the framework of data and probability statistics. Of existing non-structural components, cable tray systems are characterized by a number of uncertainties which may influence their bearing capacity drastically. In this research, the main characteristics of material, geometry, member layout along with the connection stiffness in cable tray are considered as random variables using global sensitivity analysis, with their results relative importance of these potential uncertainties on the seismic performance of cable tray. The sensitivity analysis method developed especially for cable tray under seismic excitation is constructed based on modal analysis and equivalent inertia force method combined with the Latin hypercube sampling method. The final results demonstrate the need to consider the effects of random variables in modeling assumption in seismic performance analyses of cable tray and can be further used in optimization design.